ANALISIS PENCATATAN DAN PENILAIAN PERSEDIAAN OBAT-OBATAN PADA APOTEK ALIF FARMA DI SAMARINDA - Syarifah Fauziah Dea Ariyani; Nurita Affan; Ibnu Abni Lahaya (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
Syarifah Fauziah Dea Ariyani, 2018. Analysis of Recording and Assessing Drug Supplies at Apotilk Alif Farma in Samarinda, under the guidance of Hj. Nurita AffanThe purpose of this study is to find out and analyze the recording and assessment of Alif Farma Pharmacy drug inventory if it applies Entity Financial Accounting Standards without Public Accountability (SAK ETAP).The analytical tool used is the Entity Financial Accounting Standards without Public Accountability (SAK ETAP) in 2008 concerning inventories compiled by the Financial Accounting Standards Board of the Indonesian Accountants Association.After the research process was obtained, the valuation method used by the Independent Pharmacy was not in accordance with the Entity Financial Accounting Standards without Public Accountability (SAK ETAP), wherein the evaluation of the drug inventory uses the Last In First Out (LIFO) method. With the First Entry First (MPKP) or First In First Out (FIFO) method, there is a final inventory according to different pharmacies with the ending inventory according to the existing calculation amounting to Rp. 16752,491.00 and Rp.16,911,929.00 respectively which result in the difference in the final inventory value is Rp 159,438.00, so the cost of goods sold in the income statement for the financial year ended 31 December 2013 has become too high at Rp 91,413,379.00 which should be valued at Rp 91,253,941.00 . This caused the difference in retained earnings for 2014 to increase from Rp. 34,914,775.00 to Rp. 35,074,213.00.Thus the authors suggest that Pharmacy Pharmacy Alif Arma should improve its inventory valuation system according to Entity Financial Accounting Standards without Public Accountability (SAK ETAP) regarding inventories that only use the First In First Out (FIFO) and Average valuation methods.